The Awareness Towards Quality of Service From Homestay Providers In Premium Tourism Destination - Gregorius Antariksa Berybe; Elisabeth Oktaviani Hanggu; Maria Beatrix Rahinart Wellalangi (Syntax Literate, 2021)
This research aims to know the understanding of homestay providers about the quality of service. The research design of this study is descriptive quantitative where data collected from the questionnaires that given to the homestay providers at Liang Ndara Village, Labuan Bajo, with factors of analysis are: 1) Tourism Awareness, 2) Sanitation and Hygiene, 3) Psychology of Service, 4) Guest Service and English for Communication. The result of this study shows that 84,9% of respondents are not aware of the importance of sanitation and hygiene. English as a communication shows about 78,2% of respondents are not using English as daily communication with the foreign guest. This lack of interaction because of the effect of the psychology of service (8%) of respondents are less confident having interaction. While factors shown by the respondents are highly aware such as tourism awareness (100%) and 86,9% respondents have shown their awareness of service. Providing quality of service is required commitment from respondents to aware of those factors.